Corporate social responsibility and brand loyalty in Organization for Economic Cooperation and Development - Aws AlHares (17541741) (2023)
The current study looks at how customer brand loyalty in the banking sector is impacted by perceived corporate social responsibility (CSR). The current study investigates the indirect link between CSR and brand loyalty through brand identity and believability. The causal link between perceived CSR, brand loyalty, brand identity, and brand credibility is examined. A survey of 330 banking clients in the Organization for Economic Cooperation and Development (OECD) nations was used to get the data. Further data analysis was done using AMOS version 24.0 and structural equation modeling (SEM) methods (Hamad & Cek, 2023). By examining the impact of perceived CSR, brand credibility, and brand identity on customer brand loyalty for banking services, this study broadened the conventional understanding of CSR impacts on consumers and attempted to fill a vacuum in the literature (Svetlozarova Nikolova, 2023). The study’s conclusions have important ramifications for financial organizations. These findings have implications for consumer policymakers when promoting CSR. Other Information Published in: Journal of Governance and Regulation License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.22495/jgrv12i4siart18